Relevansi Pendekatan Teori Humanistik dalam Pelaksanaan Pendidikan Inklusi: Sebuah Kajian Film Taare Zameen Par: The Relevance of Humanistic Approach Theory in the Implementation of Inclusive Education : A Study of Movie Taare Zameen Par - Wahyuni, Holy Ichda; Hendarwati, Endah (Anterior Jurnal, 2025)
Inclusive education is a form of educational service provided by the government for students with special needs. Inclusive education is a forum for equalizing the development of students' potential. Students with special needs often have obstacles in learning, such as those with dyslexia. The film Taare Zamen Par is a public exemplary media about the implementation of inclusive education and the problems that occur in dealing with children with special needs, such as the paradigm of society that still discredits children with special needs. The purpose of this study is to determine and evaluate the relevance of the humanistic theory approach in the implementation of inclusive education, through a study in the film Taare Zamen Par. This type of research is qualitative descriptive research. The method used in the analysis is the semiotic method. This study shows that the humanistic approach is relevant to be applied in the implementation of inclusive education. Referring to the results of the film review, it shows several forms of the humanistic approach, including; overcoming low self-esteem, getting to know students' personalities and their environment through sense and sensibility, building empathy, involving families as a support system, and exploring students' talents.